2021
DOI: 10.5009/gnl19402
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features of the Serrated Pathway to Colorectal Cancer: Current Knowledge and Future Directions

Abstract: Serrated lesions are the precursor lesions of a new model of colorectal carcinogenesis. From a molecular standpoint, the serrated pathway is thought to be responsible for up to 30% of all colorectal cancer cases. The three major processes of this molecular mechanism are alterations in the mitogen-activated protein kinase pathway, production of the CpG island methylation phenotype, and generation of microsatellite instability. Other contributing processes are activation of WNT, alterations in the regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…An observation about the control group showed that all BRAF -mutated SSLs without dysplasia were MSS. It is interesting to know if the evolving lesions in this group will suffer further mutations or if these lesions are going to evolve towards a BRAF -mutated MSS carcinoma, entity that has, usually, as precursor, a TSA [ 42 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…An observation about the control group showed that all BRAF -mutated SSLs without dysplasia were MSS. It is interesting to know if the evolving lesions in this group will suffer further mutations or if these lesions are going to evolve towards a BRAF -mutated MSS carcinoma, entity that has, usually, as precursor, a TSA [ 42 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…2021, 22, 6767 2 of 15 tumor cells [8]. Indeed, microsatellite sequences are tracts of tandemly repeated DNA motifs ranging from one to six nucleotides in length, which are susceptible to accumulate mutations [9].…”
Section: Introductionmentioning
confidence: 99%
“…The highest specificity and sensitivity are reached using a panel of two or more polyA mononucleotide (BAT25, BAT26, NR-21, NR-22, NR-24, and NR-27) and three dinucleotide (D2S123, D5S346, and D17S250) markers. At least two of these different markers are needed to classify the tumor as MSIhigh, whereas tumors with only one affected marker are considered MSI-low [9]. IHC is used to detect the expression of the four MMR proteins (MLH1, MSH2, MSH6, and PMS2), whose loss is highly concordant (>90%) with DNA-based assays.…”
Section: Introductionmentioning
confidence: 99%
“…Sessile serrated lesions (SSL) may be responsible for up to 35 % of colorectal cancers (CRC) 1 , through the so-called serrated pathway 2 . Because of their morphologic characteristics, they can be more easily missed or incompletely removed 3 , and some data suggest that progression to cancer may be greatly accelerated when dysplasia is already present 4 .…”
Section: Introductionmentioning
confidence: 99%